Theories of Creativity in Music: Students' Theory Appraisal and Argumentation - Huovinen, Erkki (Frontiers in Psychology, 2021)
Most research on people’s conceptions regarding creativity has concerned informal beliefs instead of more complex belief systems represented in scholarly theories of creativity. The relevance of general theories of creativity to the creative domain of music may also be unclear because of the mixed responses these theories have received from music researchers. The aim of the present study was to gain a better comparative understanding of theories of creativity as accounts of musical creativity by allowing students to assess them from a musical perspective. In the study, higher-education music students rated 10 well-known theories of creativity as accounts of four musical target activities—composition, improvisation, performance, and ideation—and argued for the “best theoretical perspectives” in written essays. The results showed that students’ theory appraisals were significantly affected by the target activities, but also by the participants’ prior musical experiences. Students’ argumentative strategies also differed between theories, especially regarding justifications by personal experiences and values. Moreover, theories were most typically problematized when discussing improvisation. The students most often chose to defend the Four-Stage Model, Divergent Thinking, and Systems Theory, while theories emphasizing strategic choices or Darwinian selection mechanisms were rarely found appealing. Overall, students tended toward moderate theory eclecticism, and their theory appraisals were seen to be pragmatic, example-based, instead of aiming for such virtues as broad scope or consistency. The theories were often used as definitions for identifying some phenomena of interest rather than for making stronger explanatory claims about such phenomena. Students’ theory appraisals point to some challenges for creativity research, especially regarding the problems of accounting for improvisation, and concerning the significance of theories that find no support in these musically well-informed adults’ reasoning.